Exploring health literacy assessment : the relexicalisation of a health literacy test from the U.S. for application in a South African population - La Rose, Christopher Michael (Rhodes University, Faculty of Humanities, Department of English Language and Linguistics, 2004)
The Rapid Estimate of Adult Literacy in Medicine (REALM) is a standardised health literacy test developed in the United States that has been previously administered and researched in South Africa (Lecoko, 2000). It is an objective vocabulary test which uses item recognition of 66 health-related words where recognition is measured by pronunciation. It is designed as a screening instrument to identifY the health literacy levels of patients in clinics. Lecoko (2000) found the REALM to be largely inapplicable in a South African setting, in that only eight out of the 66 words could be deemed acceptable, in that they could be either both adequately pronounced and adequately comprehended or both inadequately pronounced and inadequately comprehended. This may have occurred for a number of reasons, including the administration of the test in a population for whom English is a second or other language, and inaccurate measurement of pronunciation and comprehension of words, with a key problem being that the choice of words in the original REALM may not accurately represent the range of conditions and issues in a South African healthcare setting. This thesis was therefore premised on the principled relexicalisation of the REALM, that replacement of the words used in the test, using a sample gathered from health information and promotion texts in local clinics, would improve its applicability. In this regard, an exhaustive sample was gathered and analysed and 66 new words were chosen. The test was also modified to include a more principled approach to pronunciation and comprehension issues, and to account for language proficiency differences in administering an English language test in an English second language population. This modified test, referred to as the REALM-M was administered to a group of respondents who were statistically similar to the group to whom the REALM had originally been administered, and the results were compared. It was found that relexicalisation increased the number of acceptable words on the test from eight to 38. However, researching the key discourses surrounding health literacy and comparing these with current discourses about literacy beyond the field of health care revealed that despite improved content validity over the REALM, the REALM-M lacked construct validity. This provided the opportunity to discuss the discourses of health literacy and to suggest the application of alternative paradigms in this field.
Keywords: Rapid Estimate of Adult Literacy in Medicine; Educational tests and measurements; Literacy -- South Africa--Evaluation; Health education -- South Africa -- Evaluation